Effects of Futsal Sports-Specific Training on Neuromuscular Coordination in Youth Male Futsal Players - Tunintaraarj, Pongsakorn; Homsombat, Thanyawat (Journal of Health Science and Alternative Medicine, 2024)
Introduction: The studying neuromuscular coordination is integral to futsal training as it provides valuable insights into performance enhancement, injury prevention, optimized training strategies, and talent identification and development. By integrating knowledge of neuromuscular coordination into coaching and training practices, futsal teams can strive for higher levels of success on the court while minimizing the risk of injuries and maximizing the potential of their athletes. This pre-experimental research aimed to evaluate the effect of futsal sports-specific training on neuromuscular coordination in youth male futsal athletes, both before and after 4 and 8 weeks of training. Methods: The sample was obtained by calculating the sample size to estimate the average population size as the population size was known, totaling 26 youth male futsal athletes, by using a systematic random sampling method. The experiment instrument was a futsal sports-specific one that combined specific futsal training and plyometrics three days a week for eight weeks, finding the Index of item objective congruence (IOC = 1.0). The instruments used to collect data were the FAF’s slalom test to assess the change of direction and the eye-body movement test to assess the reaction time. Descriptive statistics include percentages, means, standard deviations, and inferential statistics, including one-way analysis of variance with repeated measures and the Bonferroni test, with statistical significance set at the 0.05 level. Results: The results found that the futsal athletes had a mean resting heart rate of 75.54 bpm, their heart rate during exercise was 150.16 bpm, and their RPE during exercise was 13.36. When conducting a one-way ANOVA with repeated measures, it was found that only reaction time was significantly different before, the 4th week and after the 8th week of training. Comparing the mean pair, it was found that reaction time decreased significantly both before and after the 4th week, before and after the 8th week, and after the 4th week and after the 8th week. Conclusion: Futsal sports-specific training is a complex program that influences futsal players’ performance, specifically depending on neuromuscular characteristics such as reaction time, agility, and change of direction. Keywords: Futsal sports-specific training, neuromuscular coordination, futsal player